The ASEAN agreement on transboundary haze pollution: issues of its implementation on selected polluters and affected ASEAN countries / Nor Suriani Mohd Azhar and Norsyuhaida Abd Aziz - Mohd Azhar, Nor Suriani; Abd Aziz, Norsyuhaida (2007)
This research is about a serious international issue that occurring these days which is transboundary haze pollution. The existence of the ASEAN Agreement on Transboundary Haze Pollution (hereinafter AATHP) was supposed to be the solution of the issue between ASEAN members. However, AATHP has not yet achieved its goal to prevent transboundary haze pollution. One of the reasons is because of the failure of several ASEAN members to ratify the agreement. Malaysia, Indonesia and Singapore are the ASEAN members that are badly affected by transboundary haze pollution. Thus, this research analyzed the domestic laws of these countries to see whether there are any provisions that are related to haze pollution. Furthermore, the AATHP were compared with the United Nation Convention on Long-Range Transboundary Air Pollution and the Rio de Janeiro Declaration on Environment and Development to find out whether there are any better solution in combating with the haze pollution. This researched indicated that although there are provisions in the domestic laws in these three countries studied regarding haze pollution, only Malaysia has a provision that clearly restricted open burning. Indonesia who is the major contributor to transboundary haze pollution is silent on this matter. The three agreement compared have a same objective which is to protect the environment from pollution. The Rio Declaration has the better solution by way of punishment where they adopt the polluter-pay principle. In conclusion, several changes need to be made to AATHP to make it a better agreement to settle the haze pollution.